PERANCANGAN WEBSITE JURNAL DAN LAPORAN KULIAH KERJA NYATA MAHASISWA (KNM) UNIVERSITAS MAJALENGKA TAHUN 2019 - Ridwan, Nugraha Sugiana; Mardiana, Ardi (Universitas Majalengka, 2021)
Student Real Work Lecture (KNM) is one form of devotion performed by students by giving lessons to the community in accordance with the knowledge that students have in their respective fields. During knm activities, students develop work programs that suit the needs and characteristics of the KNM implementation site accompanied by a report of work programs / KNM activities. The form of report that is still in the form of paper (manual) is considered ineffective because of limited storage space, limited availability of reports (report stock), and limited access to reports (which can only be accessed during business hours). This research was conducted with the aim to build an application that can provide convenience for students in processing KNM reports and reporting every activity during the KNM. This research study used the Rational Unified Process (RUP) and UML software development methodologies as software development models. Because the purpose in the beginning is to provide the availability of report access, the application that will be created is a web-based database application by utilizing Codeigniter Framework tools. From the research, a web-based application will be produced that can be accessed by each KNM participant.